Malignant melanoma: behavior with the nodes - D'Auria, Agustín (Cirugía del Uruguay, 1974)
Lymph node dissections prevent lymphatic disseminations in melanomas, a fact which happens in 75 % of the cases. Prophylactic in continuity dissections should be performed when the primary lies next to the regional lymph nades. Pro and con of prophylactic discontinuous dissections have been discussed for decades and are summarized here. Prospective randomized studies of the I.R.C. for melanoma of the W.H.O. will give the answer to the problem. It seems at the present time that prophylactic lymphadenectomies are not justified when the primary is distant from the regional lymph nades. Therapeutic dissections should be performed unless general disseminatiin is present. In spite of not finding the primary lesion, a dissection should be done if lymph nades are positive.